PENGARUH TERAPI BEKAM TERHADAP KADAR KOLESTEROL PADA MASYARAKAT HIPERKOLESTEROLEMIA - Yusrita, Eli; Pratama, Erwanda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Currently, health problems have shifted from infectious diseases to degenerative diseases. The cause is thought to be due to changes in lifestyle, diet, environmental factors, lack of physical activity and stress factors. Lifestyle lack of activity, consume too much food containing fat and cholesterol and lack of fiber intake can trigger degenerative diseases. A degenerative disease that significantly affects morbidity and mortality is cardiovascular disease. Research Objectives To determine the effect of cupping therapy on cholesterol levels in people with hypercholesterolemia. This research is a pre-experiment with a one group pretest-posttest research design. The results of direct examination using the GCU Easy Touch tool can be seen that out of 20 respondents. It can be seen from 20 respondents there were 17 respondents with decreased blood cholesterol levels and 3 other respondents had fixed blood cholesterol levels.Keywords: Cholesterol, Elderly, Hypercholesterolemia